2022
DOI: 10.3389/fimmu.2022.976564
|View full text |Cite|
|
Sign up to set email alerts
|

Translating the observed differences in interleukin-6 levels between some antiretroviral regimens into potential long-term risk of serious non-AIDS events: A modeling study

Abstract: IntroductionVariable levels of systemic inflammation are observed in people with HIV (PWH), but the clinical significance of differences among antiretroviral therapy (ART) regimens on associated levels of inflammatory markers is unclear. Based on data from previous epidemiologic studies that defined the predicted change in risk of serious non-AIDS events (SNAEs)/death by changes in interleukin-6 (IL-6) and D-dimer, we modeled the effects of differences in these markers between specific ART regimens on the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We planned this study given the potential clinical implications of the data, first reported by Serrano-Villar et al. ( 18 ) and later published in 2022 ( 7 , 8 ) endorsed by other expert opinions ( 5 , 6 ), suggesting that switching to 2DR was associated with a worse long-term inflammatory profile.…”
Section: Discussionmentioning
confidence: 98%
“…We planned this study given the potential clinical implications of the data, first reported by Serrano-Villar et al. ( 18 ) and later published in 2022 ( 7 , 8 ) endorsed by other expert opinions ( 5 , 6 ), suggesting that switching to 2DR was associated with a worse long-term inflammatory profile.…”
Section: Discussionmentioning
confidence: 98%
“…This approach was selected as we assumed that most PWH who achieve viral suppression are highly adherent to ART at some point during the course of their treatment (eg, early stage of treatment initiation) [ 24 , 25 ], but that a decrease in adherence—without the development of viremia—is expected in some patients [ 2 , 3 ]. To achieve this, we used a simplified version of the Markov model developed by Serrano-Villar et al [ 26 ], where we inputted the change in biomarkers available in the literature to estimate the number of PWH who would need to reduce adherence before an additional SNAE or death is observed. This model relied on previously published Kaplan-Meier curves illustrating the cumulative number of participants with an event by IL-6 quartile [ 20 ], with separate Weibull distributions fit to each quartile specific curve, from which in-year probabilities of a SNAE or death were derived.…”
Section: Methodsmentioning
confidence: 99%
“…This model relied on previously published Kaplan-Meier curves illustrating the cumulative number of participants with an event by IL-6 quartile [ 20 ], with separate Weibull distributions fit to each quartile specific curve, from which in-year probabilities of a SNAE or death were derived. In addition to the model by Serrano-Villar et al [ 26 ], we utilized least squares optimization to fit gamma distributions to IL-6 quartiles published by Grund et al [ 20 ], and subsequent movement between quartiles was based on previously reported elevated plasma IL-6 levels for those with <100% ART adherence. We assumed a one-time increase in plasma IL-6 with subsequent events predicted over a 3- or 5-year follow-up.…”
Section: Methodsmentioning
confidence: 99%